Pengaruh Praktik Kewirausahaan terhadap Motivasi Berwirausaha Peserta Didik - Yuni Kartika; Bambang Genjik Sumartono; Syamsuri Syamsuri (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
Instilling entrepreneurial motivation in students is an important thing that takes advantage of the role of entrepreneurial practices in schools in creating many young entrepreneurs in the future. This study aimed to see the entrepreneurial practices and entrepreneurial motivation of class XII Accounting students at SMK Negeri 7 Pontianak and how much influence the entrepreneurial practices have on the students’ entrepreneurial motivation. The research approach used is a quantitative approach with a correlational method. This research took 64 students as research participants. The data analysis used is descriptive statistics and simple linear regression. The research findings show that the entrepreneurial practices perception is exceptionally high, the students’ entrepreneurial motivation is very high, and the entrepreneurial practices significantly affect entrepreneurial motivation. The effect was about one-third, while the rest was influenced by variables that have not been studied, such as curriculum, entrepreneurship learning models, and the family environment that should become recommendations for further researchers to examine them.